STUDENTS AWARENESS TOWARDS ENTREPRENEURSHIP: A STUDY BASED ON CENTRAL KERALA - Alphin T Kallany and Suresh T S
Many studies show that entrepreneurs shape economic destiny of nations by creating wealth and employment, offering products and services and generating taxes for Gov. because of which entrepreneurship has closely linked to economic growth of a country (Kumari Indra,2014). An attempt is made in this paper to measure the level of awareness about entrepreneurship among students. To examine the hypothesis data was gathered from self- administrated questionnaire conducted in college students in central Kerala consisting of 213 samples. The descriptive analysis of data shows that the the students are aware about the term ‘Entrepreneurship’ irrespective of gender difference where Commerce students seemed to be more aware than students in another stream. The respondents are unaware about the legal formalities for starts ups and entrepreneurial supporting schemes of Gov.